Intuitionistic fuzzy sets theory and applications - Atanassov Krassimir T (Heidelberg Physica-Verlag, 1999)
Discusses some of the IFS extensions and applications. Attempts a comprehensive and complete report on the intuitionistic fuzzy set theory and its more relevant applications in a variety of diverse fields.
Keywords: Fuzzy sets